2018
DOI: 10.3389/fpsyt.2018.00651
|View full text |Cite
|
Sign up to set email alerts
|

The Orbitofrontal Cortex Gray Matter Is Associated With the Interaction Between Insomnia and Depression

Abstract: Insomnia and depression are highly comorbid symptoms in both primary insomnia (PI) and major depressive disorder (MDD). In the current study, we aimed at exploring both the homogeneous and heterogeneous brain structure alteration in PI and MDD patients. Sixty-five MDD patients and 67 matched PI patients were recruited and underwent a structural MRI scan. The subjects were sub-divided into four groups, namely MDD patients with higher or lower insomnia, and PI patients with higher or lower severe depression. A g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 58 publications
(63 reference statements)
0
34
1
Order By: Relevance
“…This combination of symptom may be the result of a peculiar etiopathology or of the presence of different, concomitant factors. Previous studies reported sleep onset insomnia increasing the risk for debilitating mental problems (Canivet et al, 2014) while neuroimaging brings evidence of a connection between early morning awakenings and depression (Stoffers et al, 2012;Yu et al, 2018). Speculatively, it is possible that the two insomnia symptoms and depression are connected in a consecutive and escalating manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This combination of symptom may be the result of a peculiar etiopathology or of the presence of different, concomitant factors. Previous studies reported sleep onset insomnia increasing the risk for debilitating mental problems (Canivet et al, 2014) while neuroimaging brings evidence of a connection between early morning awakenings and depression (Stoffers et al, 2012;Yu et al, 2018). Speculatively, it is possible that the two insomnia symptoms and depression are connected in a consecutive and escalating manner.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, magnetic resonance imaging (MRI) studies seems to support biological differences for individual insomnia symptoms, as orbitofrontal grey matter appeared reduced only in patients experiencing early morning awakenings (Stoffers et al, 2012). The DSM-5 report specifically this nocturnal symptom of insomnia among the diagnostic criteria for melancholic depression and indeed patients with comorbid depression and insomnia show also reduced grey matter in the OFC (Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to the findings reported by Takeucki and colleagues [28] who observed an association between eveningness and lower grey matter volume in in orbitofrontal cortex and Rosenberg et al [29], who observed no between-group differences in these regions. Lower lateral orbitofrontal grey matter volume has been observed in substance use disorder [56,57], substance dependence [58], a number of psychiatric disorders including depression [59,60] and internet-gaming disorder [61]. Eveningness has also been associated with substance use [48,49], depression [22,[62][63][64] and with increased mobile-phone gaming [65].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study was a preliminary exploration of the pathogenesis of insomnia (rather than CID with GI disorder) in terms of brain function and structure. [20][21]50] Other research teams have con rmed that insomnia patients have abnormal brain metabolism using MRS technology. [24][25][26] At present, there are no brain imaging studies on patients with CID with GI.…”
Section: Discussionmentioning
confidence: 99%
“…Using fMRI, we previously con rmed that the core pathological features of patients with CID are evident in the structural and functional plasticity of the brain. [20][21] Some DTI research indicates that the white matter tracts in the anterior internal capsule, right arcuate fasciculus, and superior longitudinal fasciculus of patients with insomnia are abnormal. [22][23] MRS is the only noninvasive method that can quantify biochemical substances in the brain, [24] and MRS studies have identi ed abnormal brain metabolic activity in insomnia patients.…”
Section: Introductionmentioning
confidence: 99%